Awareness and knowledge of social protectionsamong gig economic workers in kota bharu, kelantan: a qualitative study - Siti Aisyah Azman; Siti Farzzanah Kader Ibrahim; Siti Sarah Aqilah Rudisham; Harini A/P Harikrishnan (2022)
This study aimed to explore and analyze the level of awareness regarding social protection among gig economy workers in Kota Bharu, Kelantan. The primary objective of this research was to assess the knowledge of social protection among gig economy workers in the selected region. The study employed a qualitative analysis approach, utilizing personal semi-structured interviews as the primary method of data collection. Eight respondents, who were food delivery riders, participated in the interviews, providing valuable insights and perspectives.The use of personal semi-structured interviews allowed for a comprehensive understanding of the respondents' experiences, opinions, and beliefs regarding social protection. The method facilitated an open and honest exchange of information, ensuring the collection of reliable and authentic data for this research paper. The findings of this study contribute to the existing body of knowledge on gig economy workers and their awareness of social protection in Kota Bharu, Kelantan. By exploring the perspectives of food delivery riders, this research sheds light on their understanding of social protection and the challenges they face in accessing it. The results provide valuable insights into the current state of social protection awareness among gig economy workers and can guide future researchers in conducting similar studies.The implications of this study extend beyond its immediate scope. The findings can inform policymakers, employers, and relevant stakeholders about the importance of social protection for gig economy workers. Additionally, the study emphasizes the need to address any gaps in knowledge and access to social protection, aiming to enhance the overall well-being and security of gig economy workers in Kota Bharu, Kelantan.In conclusion, this research endeavors to deepen the understanding of social protection awareness among gig economy workers in Kota Bharu, Kelantan. The use of qualitative analysis and personal semi-structured interviews provides valuable insights into the knowledge and experiences of food delivery riders. The findings of this study can be utilized by future researchers and stakeholders seeking to improve the social protection measures for gig economy workers in the region.